Gastrointestinal mixed neuroendocrine carcinoma: Case reports and review of literature - Hanumappa, Harish Kumar; D’Souza, Dyan; Rao, Joseph Sushil; Naduvathkundil, Faslu Rahman; Chowdappa, Raghunandan Gorantlu; Joseph, Elvis Peter (Indian Journal of Case Reports, 2018)
Mixed adenoneuroendocrine carcinoma (MANEC) is a rare and relatively newer entity and classified into a separate category by the WHO 2010 Classification of Tumors. Accordingly, due to its rarity of diagnosis, further oncologic management is a challenge. They contain an adenocarcinoma part and a neuroendocrine part and are further classified based on grades. We present case series with a histological diagnosis of MANEC, its management, and clinical behavior in the follow-up period. Optimum mode of the management of these tumors is yet to be proposed, as these groups of tumors are highly aggressive and associated with poor prognosis.